Pulmonary Thromboembolism in a Child with Sickle Cell Hemoglobin D Disease in the Setting of Acute Chest Syndrome - Hazel Villanueva; Sandeepkumar Kuril; Jennifer Krajewski; Aziza Sedrak (Hindawi Limited, 2013)
Introduction. Sickle cell hemoglobin D disease (HbSD) is a rare variant of sickle cell disease (SCD). Incidence of pulmonary thromboembolism (PE) and deep venous thrombosis (DVT) in children with HbSD is unknown. PE and DVT are known complications of SCD in adults but have not been reported in the literature in children with HbSD. Case Report. We are reporting a case of a 12-year-old boy with HbSD with acute chest syndrome (ACS) complicated by complete thrombosis of the branch of the right pulmonary artery and multiple small pulmonary artery emboli seen on computed tomography (CT) pulmonary angiogram and thrombosis of the right brachial vein seen on Doppler ultrasound. Our patient responded to treatment with anticoagulant therapy. Conclusion. There are no cases reported in children with HbSD disease presenting as ACS with pulmonary thromboembolism. We suggest that PE should be suspected in patients presenting with ACS who do not show improvement with standard management. CT pulmonary angiogram should be utilized for early diagnosis and appropriate management as there is no current protocol for management of PE/DVT in pediatric patients with SCD.